Leveraging Social Change Through Collective Purchasing - Holly A. Chaille (Journal of Agriculture, Food Systems, and Community Development, 2016)
In the dedication page of Beyond Alternative Food Networks, Grasseni quotes from Immanuel Kant's Critique of Pure Reason: "There can be no doubt that all our knowledge begins with experience." Her selection may serve as an indicator that Grasseni's experience as a member of a solidarity purchase group (a group of people who purchase directly from growers and producers) is the basis for her argument that these community collaboratives can be powerful structures for addressing and improving more than local food issues. A conscientiously systematic and democratic approach that stresses inclusion as opposed to homogeneity, she posits, can be applied more broadly within communities to address economic sustainability.